MAXIMUM BACKPACK WEIGHT RECOMMENDED FOR CHILDREN IN SCHOOL CONTEXT: A SCOPING REVIEW - Maria João Matos; Catarina Barreiras; Constança Festas (Revista Portuguesa de Enfermagem de Reabilitação, 2020)
Objectives: to map the evidence in relation to the maximum backpack weight recommended for children in school context.